2001
DOI: 10.1086/321787
|View full text |Cite
|
Sign up to set email alerts
|

The Absolute Cross Section forL‐Shell Photoionization of C+Ions from Threshold to 105 eV

Abstract: The absolute cross section for photoionization of C`ions has been measured from the ionization threshold at 24 eV to 105 eV by overlapping an ion beam with a monochromatized synchrotronradiation beam from the ASTRID undulator. The measurements, which are important for astrophysical modeling of, for example, stellar atmospheres, have been compared with R-matrix calculations from the Opacity Project and the Iron Project. The general agreement between theory and experiment is good, yet di †erences in the magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…The allowed one-electron transitions involving 2s electrons are 2s 2 2p 2 P + hν → 2s2p( 1,3 P)np 2 S, 2 P, 2 D. The 2 P terms cannot Coulomb autoionize into the 1s 2 2s 2 1 S + p continuum, however previous studies (see e.g. Kjeldsen et al 1999a) showed that these states were indeed responsible for peaks in the photoionization spectrum, and their presence has been attributed to the influence of relativistic effects in the case of C + (Kjeldsen et al 2001). Thus, we can expect the presence of 6 Rydberg series converging to the 1 P and 3 P limits of the 2s2p core.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The allowed one-electron transitions involving 2s electrons are 2s 2 2p 2 P + hν → 2s2p( 1,3 P)np 2 S, 2 P, 2 D. The 2 P terms cannot Coulomb autoionize into the 1s 2 2s 2 1 S + p continuum, however previous studies (see e.g. Kjeldsen et al 1999a) showed that these states were indeed responsible for peaks in the photoionization spectrum, and their presence has been attributed to the influence of relativistic effects in the case of C + (Kjeldsen et al 2001). Thus, we can expect the presence of 6 Rydberg series converging to the 1 P and 3 P limits of the 2s2p core.…”
Section: Resultsmentioning
confidence: 95%
“…Also, this division facilitates the discussion. The emphasis will be on the threshold regions, but the complete data sets can be obtained (Kjeldsen et al 1999a(Kjeldsen et al , 2001, N 2+ (Bizau et al 2004, only relative data) and O 3+ (Champeaux et al 2003). In the last two cases the data were measured utilizing a different set-up at the storage ring SuperACO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of the excellent agreement achieved between theory and experiment has been noted for the lighter systems B 2+ and N + (Müller et al 2010;Gharaibeh et al 2011) during K-shell photoionization. In addition, poor agreement at higher photon energies was found between OP results and experimental photoioniza-⋆ E-mail: ntyndall01@qub.ac.uk tion cross sections for C + (Kjeldsen et al 2001). This reinforces the need to conduct sophisticated R-matrix calculations on high performance computing facilities to match advancements in experimental technologies.…”
Section: Introductionmentioning
confidence: 99%